Prevalence of two economically significant viral pathogens wssv and ihhnv in farming systems of the exotic shrimp species penaeusvannamei(boone, 1931) in southeast coast of India - M. C. REMANY,; R. KIRUBAGARAN,; JAIDEEP KUMAR, (International Journal of Pharma and Bio Sciences, 2016)
Penaeus vannamei (Pacific white legged shrimp), is an exotic shrimp species introduced to India in 2009, and is currently been extensively cultured along the Southeast coastal region of the Country. The expansion of the industry had resulted in mushrooming up of unapproved hatcheries and farms which do not implement adequate biosecurity measures or good management practices required for farming this exotic shrimp species. This resulted in frequent disease outbreaks which in turn resulted in crop loss to the industry. The present study highlights the investigation on the prevalence of economically significant DNA and RNA viral pathogens [(White Spot Syndrome Virus (WSSV) and Infectious Hypodermal Haematopoietic Necrosis Virus (IHHNV), Taura Syndrome Virus (TSV) and Infectious Myonecrosis Virus (IMNV)] in P. vannamei cultured in approved and unapproved farming systems along the two major coastal regions (Andhra Pradesh and Tamil Nadu) of Southeast India. Overall prevalence of WSSV and IHHNV pathogens was higher (p<005) in unapproved farms than the approved ones. However prevalence was not found to be statistically different between the two coasts. Data on prevalence of these pathogens in the farming systems would be useful to develop strategies for shrimp health management and thus serve to formulate mitigation measures to control the disease incidences in P. vannamei farming systems of the Country.